Role of Transvaginal Ultrasound in Management of Abnormal Uterine Bleeding - Din Muhammad Sohu, Bhagwan Das, Muhammad Rashid Rasul, Imran Khan Memon, Inayatullah, Rabia HafeeZ, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the transvaginal ultrasound in management of abnormal uterine bleeding. Place and duration of study: Department of Radiology, Ghulam Muhammad Mahar Medical College Hospital Sukkur from 1st July 2021 to 31st December 2021. Methodology: In this prospective study one hundred patients were enrolled. The patients were scrutinized on bases of their abnormal uterine bleeding and underwent transvaginal ultrasound. The clinical and demographic information was recorded and the sonographic results were evaluated. Results: There was no significant difference of age with the number of their births. Menorrhagia was observed in 13% while 57(57%) had metrorrhagia and 30% were having menometrorrhagia. The abnormal uterine bleeding diagnosis was made and it was seen that 61% leiomyoma, 22% polyp, 12% adenomyosis and 5% endometrial adenocarcinoma cases were presented respectively. Within these cases endometrial adenocarcinoma had transvaginal scan sensitivity of 100% followed by leiomyoma as 93% transvaginal scan sensitivity in cases. Conclusion: Transvaginal ultrasound is an efficient way of managing abnormal uterine bleeding.